The moderating roles of organizational culture and learning orientation on the relationship between individual market orientation and job performance / Muhammad Iskandar Hamzah - Hamzah, Muhammad Iskandar (2017)
The scope of this study is focused on business-to-business (B2B) salespeople of financial institutions, often referred to as Relationship Managers (RM). As representatives who represent their firm, RMs' performance is guided by their behaviour pertaining to customer knowledge. Previous researches within the field of knowledge management (KM) emphasized on the organizational knowledge and its application in firms' learning process and performance. Lately, there has been a growing emphasis positioned on both knowledge management and customer relationships, which are referred to as customer knowledge management (CKM). CKM is viewed as an enhancement of KM practices that focuses on the understanding of the customers' needs and wants to build sustained customer relationships. However, little has been known so far on the roles of customer knowledge within individuals' social psychology contexts, where traditional relational marketing activities are the focal areas of research interest compared to IT-driven marketing processes. Furthermore, there are gaps in the literature to empirically support the customer knowledge-oriented behaviour construct at the individual level. Due to the fact that customer knowledge is embedded in both marketing and knowledge management activities, existing and relevant models on market orientation and CKM were reviewed and assimilated to justify the use of the individual market orientation (I-MARKOR) construct, in order to fill such knowledge voids. In this regard, individual market orientation appears to be a manifestation of customer knowledge-based conduct that involves acquisition, dissemination and strategic responses to customer knowledge. Based upon the tenets of Social Cognitive Theory and Knowledge Theory, an empirical model that analyses direct relationship between job performance and individual market orientation variables is established. The moderating roles of organizational culture (external environment) and learning orientation (individual cognitive differences) on the abovementioned relationship are also investigated. Results from a field study involving 539 RMs from 18 banks across the Klang Valley demonstrate evidence for construct validity and reliability. In terms of direct causal-outcome models, five out of nine hypothesized direct relationship between I-MARKOR and job performance variables are found to be significant. In terms of testing the hypothesized contingent relationships, moderated regression analyses were conducted using Hayes' PROCESS macro tool. Among the five moderator constructs, only Adhocracy and Group Culture are found to have moderating effects on the I-MARKOR and job performance links. The statistical findings are further illustrated using conditional effect diagrams via Johnson Neyman technique to visualize and understand whether the interactions are either significant across all values or certain values of the moderating variables. Thus, this research contributes to the existing literature by modelling individual market orientation conduct as predictors of job performance that is contingent upon inculcation of certain cultural values in the workplace. Theoretical and practical implications were discussed to provide insights for future research in this area.